Evaluation of hydrolyzed salmon and hydrolyzed poultry feather diets in restrictive diet trials for diagnosis of food allergies in pruritic dogs - Lewis, Thomas P.; Moore, George E.; Laporte, Carine; Daristotle, Leighann; Frantz, Nolan Z. (Frontiers in Veterinary Science, 2025)
IntroductionCanine cutaneous adverse food reaction (CAFR) is a common disorder caused by abnormal and unwanted skin reactions to ingested dietary allergens. Whereas other forms of allergic dermatitis may require drug therapy, CAFR is best treated with dietary change. Therefore, early and accurate diagnosis and treatment of CAFR are critical. The gold standard test for CAFR is a 6–12 week elimination diet trial using limited and known hypoallergenic proteins.MethodA multicenter, triple-blinded, randomized, crossover prospective clinical study was conducted in dogs suspected to have cutaneous adverse food reaction. The study utilized a hydrolyzed salmon (HS) diet and a hydrolyzed poultry feather (HPF) diet in separate elimination diet trials to determine if the HS diet would be efficacious and well-tolerated, compared with the established HPF diet, to diagnose and treat CAFR.ResultsFifty-seven dogs were enrolled, and 47 dogs completed the study. HS was well-tolerated, similar to HPF. Pruritus scores during the initial elimination diet trial were reduced with both diets, and dermatitis severity scores during both diet trials were reduced with both diets in the 47 dogs diagnosed with either CAFR, CAFR with atopic dermatitis (AD), or AD. Over half of the subjects diagnosed with CAFR or CAFR with AD required >4 weeks to show PVAS score decreases ≥2 or any decrease in CADESI-4 score.DiscussionHS, like HPF, presents a valuable diagnostic and treatment tool for dogs suffering from CAFR. Both hydrolyzed diets tested also improved clinical signs in dogs diagnosed with AD and may be useful adjunctive tools in the management of canine AD.